2022
DOI: 10.3389/fpubh.2022.963667
|View full text |Cite
|
Sign up to set email alerts
|

Kidney health in the COVID-19 pandemic: An umbrella review of meta-analyses and systematic reviews

Abstract: BackgroundThis umbrella review aims to consolidate evidence from systematic reviews and meta-analyses investigating the impact of the coronavirus disease−2019 (COVID-19) on kidney health, and the associations between kidney diseases and clinical outcomes in COVID-19 patients.MethodsFive databases, namely, EMBASE, PubMed, Web of Science, the Cochrane Database of Systematic Reviews and Ovid Medline, were searched for meta-analyses and systematic reviews from January 1, 2020 to June 2, 2022. Two reviewers indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 87 publications
0
10
0
1
Order By: Relevance
“…Several studies have reported a significant association between CKD and adverse clinical outcomes, including higher rates of hospitalization, ICU admission, and mortality in COVID-19 patients with preexisting kidney disease. 43,44 CKD has been identified as an independent risk factor for COVID-19 severity, with decreased kidney function correlating with worse outcomes. 45 Moreover, CKD patients on maintenance dialysis have been reported to be particularly vulnerable, with an increased risk of complications and mortality compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported a significant association between CKD and adverse clinical outcomes, including higher rates of hospitalization, ICU admission, and mortality in COVID-19 patients with preexisting kidney disease. 43,44 CKD has been identified as an independent risk factor for COVID-19 severity, with decreased kidney function correlating with worse outcomes. 45 Moreover, CKD patients on maintenance dialysis have been reported to be particularly vulnerable, with an increased risk of complications and mortality compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that individuals with CKD and liver disease are at a higher risk of severe outcomes when infected with COVID‐19. Several studies have reported a significant association between CKD and adverse clinical outcomes, including higher rates of hospitalization, ICU admission, and mortality in COVID‐19 patients with preexisting kidney disease 43,44 . CKD has been identified as an independent risk factor for COVID‐19 severity, with decreased kidney function correlating with worse outcomes 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Her daily urine volume was 1,500-2,000 mL. Laboratory data showed that her hemoglobin, platelet count, and serum creatinine were 98 g/L, 142×10 9 /L, and 238 µmol/L, respectively. She continued to receive hormonal therapy, antacid, blood pressure lowering agents, antiplatelet therapy, and treatment for anemia.…”
Section: Case Presentationmentioning
confidence: 99%
“…У цьому дослідженні кількість хворих серед чоловіків на 12 % перевищувала таку в жінок, а серед людей з ХХН -лише на 3 %. Відомо, що особи чоловічої статі мають вищі рівні рецептора АПФ-2, зокрема, такий феномен є у людей із серцевою недостатністю [10]. SARS-CoV-2 використовує саме рецептор АПФ-2 для входу в клітину і агресивніший варіант Delta, що містить багато мутацій в субодиниці S 1 , поліпшує його здатність зв'язуватися з АПФ-2 [11].…”
Section: обговоренняunclassified